Jurnal Kata: gypsies in 19 th century french literature: the paradox in centering the periphery - Udasmoro, W. (Prodi Bahasa Inggris Fak sastra PETRA, 2015)
the issues of liberty and views of the other were common in 19 century french literature discourse, in many aspects